Quantum pressure focusing in solids: a reconstruction from experimental electron density. Issue 2 (9th April 2019) - Tsirelson, Vladimir G.; Stash, Adam I.; Tokatly, Ilya V.
Abstract : The indicator of quantum pressure focusing (IQPF) displays the inner‐crystal regions where the electronic pressure is concentrated or depleted due to the quantum kinetic, exchange and correlation effects. It reveals the chemical bond features in crystals, using orbital‐free formalism of the density functional theory in combination with experimental electron density. Abstract : Here an approach is presented for reconstructing the distribution of electronic internal quantum pressure in the electronic continuum of solids from the experimental electron density. Using the formalism of the density functional theory, the spatial inner‐crystal map of the quantum pressure is obtained. The results are visualized via the indicator of quantum pressure focusing (IQPF) which reveals the regions where the pressure is concentrated or depleted due to quantum effects. IQPF contains all quantum electron‐shell structure‐forming contributions resulting from kinetic, exchange and correlation effects, and presents a clear picture of the chemical bond features in crystals with different type of bonding mechanisms.